Structural basis for pH gating of plant aquaporins. Issue 7 (27th February 2013) - Frick, Anna; Järvå, Michael; Törnroth-Horsefield, Susanna
Abstract : Plants have evolved to cope with fluctuations in water supply by gating their water channels known as aquaporins. During flooding, a rapid drop of cytosolic pH due to anoxia leads to a simultaneous closure of the aquaporins in the plasma membrane. The closing mechanism has been suggested to involve a conserved histidine on cytosolic loop D. Here we report the crystal structure of a spinach aquaporin at low pH, revealing for the first time the structural basis for how this pH‐sensitive histidine helps to keep the aquaporin in a closed state. Abstract : ► Crystal structure of the spinach aquaporin SoPIP2;1 at 3.1 Å resolution. ► Structural basis for pH gating of plant aquaporins is described. ► The pH‐sensitive residue is a fully conserved histidine in the cytoplasmic loop D. ► The pH‐sensitive histidine interacts with loop B. ► This interaction helps to maintain the water channel in a closed state.